Pengaruh Skeptisisme Profesional, Independensi, Dan Etika Pemeriksa Terhadap Perilaku Kognitif Pemeriksa Pada BPK Perwakilan Provinsi Sulawesi Selatan - Andi Pallawagau; Syamsuri Rahim; Juliyanty Sidik Tjan (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
ABSTRACT Public sector auditing plays an important role in ensuring accountability and transparency in public financial management. In performing audit assignments, auditors of the Supreme Audit Institution of Indonesia (Badan Pemeriksa Keuangan/BPK) are required not only to possess technical competence but also cognitive abilities in evaluating information, assessing evidence, and making professional judgments. Auditors’ cognitive behavior may be influenced by internal factors, including professional skepticism, independence, and auditor ethics. This study aims to examine the effect of professional skepticism, auditor independence, and auditor ethics on auditors’ cognitive behavior at the Audit Board of the Republic of Indonesia Representative Office of South Sulawesi Province. This study employed a quantitative approach with a causal research design. The population consisted of auditors at the BPK Representative Office of South Sulawesi Province, while the sample was selected using purposive sampling. Data were collected through questionnaires using a five-point Likert scale. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 through outer model evaluation, inner model analysis, and bootstrapping for hypothesis testing. The results indicate that professional skepticism has a positive and significant effect on auditors’ cognitive behavior, with a path coefficient of 0.437 and a p-value of 0.015. Auditor independence also has a positive and significant effect on cognitive behavior, with a path coefficient of 0.616 and a p-value of 0.000. Meanwhile, auditor ethics has a significant negative effect on auditors’ cognitive behavior, with a path coefficient of -0.065 and a p-value of 0.017. Furthermore, the R-square value of 0.980 indicates that professional skepticism, auditor independence, and auditor ethics explain 98% of the variance in auditors’ cognitive behavior. This study demonstrates that improving auditors’ cognitive behavior at BPK requires strengthening professional skepticism, maintaining auditor independence, and implementing ethical values beyond formal compliance. Therefore, improving audit quality should not only focus on procedural compliance but also on developing critical thinking abilities and professional judgment among auditors. Keywords: Professional Skepticism, Auditor Independence, Auditor Ethics, Auditor Cognitive Behavior, Supreme Audit Institution